Interacted multiple ant colonies optimization approach for the single machine total weighted tardiness problem - Aljanaby, Alaa; Ku-Mahamud, Ku Ruhana (2011)
Single Machine Total Weighled Tardiness problem (SMTWTP) is an important combinatorial optimization problem that considers the Job scheduling for sequential processing on a single machine and the target is to minimize the total tardiness of all jobs. This is a crucial task in manufacturing and production planning. The framework of lnteracted Multiple Ant Colonies Optimization (IMACO) is a recent proposition. It divides the ants' population into several colonies and employs certain techniques to organize the work of these colonies. This paper considers the tackling of SMTWTP using IMACO. It also proposes the idea of different ant colonies use different types of problem dependent heuristics. The performance of IMACO was demonstrated and compared with the best performing ant algorithms the Ant Colony System (ACS). The Computational results show the dominance of IMAGO.